Layout design for food safety improvement of frozen crispy chicken curry puff processing - Rosli, Nur Amira; Mahyudin, Nor Ainy; Selamat, Jinap; Mahmud Ab Rashid, Nor Khaizura (Universitatea "Dunarea de Jos" din Galati, 2022)
Cross movement between workstations, and inefficient material flow during the production process results in cross-contamination of food products. The purpose of this study is to develop a new layout design for a SME manufacturing frozen crispy chicken curry puff in Malaysia. Facility Sanitary Design Checklist was used in evaluating the establishment of hygiene zone, and workers and material flow. A new layout was developed using activity relationship analysis. The result revealed that hygiene zone establishment of the existing layout was 38.5%. The worker and material flows were poorly controlled with a score of 22.5%. The workstation arrangement in the new layout was developed in the true order of product flow based on closeness rating. The new layout scores higher marks in the application of hygiene zone (78.8%) and worker and material flow (90%) in most criteria compared to the existing layout. The new layout created new workstations and provided new facilities such as a separate change room, travel pathway, and access to high hygiene zone areas to avoid contamination risk and mix of worker traffic. Overall, new layout development produced an improved layout design in terms of workstation arrangement, hygiene zone segregation, and worker and material flow in solving SME layout problems.